2012
DOI: 10.4103/0972-124x.100911
|View full text |Cite
|
Sign up to set email alerts
|

Salivary enzymes as diagnostic markers for detection of gingival/periodontal disease and their correlation with the severity of the disease

Abstract: Context:Host responses to periodontal disease include the production of different enzymes released by stromal, epithelial or inflammatory cells. Important enzymes associated with cell injury and cell death are aspartate aminotransferase, alanine aminotransferase (AST, ALT), alkaline phosphatase, acidic phosphatase (ALP, ACP), and gama glutamyl transferase (GGT). Changes in enzymatic activity reflect metabolic changes in the gingiva and periodontium, in the inflammation.Aims:In this article we examined the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
31
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 15 publications
(20 reference statements)
3
31
1
8
Order By: Relevance
“…20 Furthermore, various studies have shown that altered salivary pH, BC and ALP levels are associated with the formation or development of dental caries, gingivitis, periodontitis, human immunodeficiency virus (HIV) infection, diabetes, orthodontic tooth movements, cancer, abdominal inflammatory diseases and the early onset of menopause. 3,4,12,13,[21][22][23][24][25][26][27][28][29] In the current study, salivary pH was lower among smokers in comparison to non-smokers; although the mean values found seem to reflect a minimal difference between the two groups (7.42 versus 7.52, respectively), even very small alterations in pH can influence salivary enzyme activity. 6 Additionally, BC was significant lower among smokers in the current study.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…20 Furthermore, various studies have shown that altered salivary pH, BC and ALP levels are associated with the formation or development of dental caries, gingivitis, periodontitis, human immunodeficiency virus (HIV) infection, diabetes, orthodontic tooth movements, cancer, abdominal inflammatory diseases and the early onset of menopause. 3,4,12,13,[21][22][23][24][25][26][27][28][29] In the current study, salivary pH was lower among smokers in comparison to non-smokers; although the mean values found seem to reflect a minimal difference between the two groups (7.42 versus 7.52, respectively), even very small alterations in pH can influence salivary enzyme activity. 6 Additionally, BC was significant lower among smokers in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…23 Higher salivary ALP levels have also been found among individuals with periodontal disease, pancreatitis and appendicitis, with treatment of the disease resulting in lowered enzyme levels. 3,4,29 Therefore, non-invasive assessment of ALP levels may be useful in the diagnosis and prognosis of periodontal tissue function and treatment monitoring of abdominal inflammatory diseases. 3,29 Smoking has been found to cause periodontal disease and bone destruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations